2019
DOI: 10.1002/fsn3.1252
|View full text |Cite
|
Sign up to set email alerts
|

Rumen biohydrogenation of linoleic and linolenic acids is reduced when esterified to phospholipids or steroids

Abstract: Manipulation of rumen biohydrogenation (BH) is of great importance, since decreased BH of linolenic acid (LNA) and linoleic acid (LA) is linked to increased content of the beneficial polyunsaturated fatty acids (PUFA) in dairy products and decreased content of trans fatty acids (FAs). We hypothesized that PUFA esterified to the complex lipid fractions are less prone to BH compared with PUFA esterified to the simple lipid fractions due to reduced lipolysis. In vitro rumen BH of different single lipid fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Some C18: 3n -3 was removed with the hull, causing a decline in the C18: 3n -3 proportion of the FA intake. Despite the effect of treatments, unexpected lower BH of C18: 3n -3 compared with C18: 2n -6 in our study could be due to the nature of the oat fat, which is rich in phospholipids (Kaimainen et al, 2012), as BH of C18: 3n -3 was shown to be lower when esterified to phospholipids (Lashkari et al, 2019).…”
Section: Digested Amount and Digestibilitycontrasting
confidence: 83%
“…Some C18: 3n -3 was removed with the hull, causing a decline in the C18: 3n -3 proportion of the FA intake. Despite the effect of treatments, unexpected lower BH of C18: 3n -3 compared with C18: 2n -6 in our study could be due to the nature of the oat fat, which is rich in phospholipids (Kaimainen et al, 2012), as BH of C18: 3n -3 was shown to be lower when esterified to phospholipids (Lashkari et al, 2019).…”
Section: Digested Amount and Digestibilitycontrasting
confidence: 83%
“…Due to the pathway involved in biohydrogenation, the main CLA escaping the rumen are cis-9, trans-11 and trans-9, trans-11 while trans-11 is the most abundant from C18:1, but many more positional and geometric isomers of CLA outflow the rumen and are present in milk of dairy cows [11,16]. A very recent study demonstrated that PUFA esterified to more complex lipids, such as phospholipids and cholesterol esters proportionally abundant in forages, are less prone to biohydrogenation compared to PUFA esterified to TAG, abundant in seeds and derived oil [17]. Findings from that study can have important implication in feeding dairy cows to increase enrichment of PUFA in milk.…”
Section: Biohydrogenationmentioning
confidence: 99%
“…The biohydrogenation of C18:3 in the rumen is decreased when this FA is associated with the membrane fraction [343]. Recent in vitro data demonstrated that biohydrogenation of PUFA is decreased when associated with complex lipid fractions, such as phospholipids and cholesterol ester, compared to simple lipid fractions, such as TAG [17]. The utilization of FA from grazing plants is also determined by the composition of the pastures.…”
Section: Role Of Dietary Fatty Acids On Milk Fat Compositionmentioning
confidence: 99%
“…For instance, Butyrivibrio fibrisolvens was found to hydrolyse predominantly phospho-and galactolipids in the rumen, whereas also other bacteria such as Anaerovibrio lipolyticus are able to hydrolyse triacylglycerols (Enjalbert et al, 2017). Consequently, FAs esterified to phospholipids are less intensively biohydrogenated in the rumen compared to other lipid fractions (Lashkari et al, 2019). Eventually, the biohydrogenation of ALA, in particular its isomerisation to C18:3c9,t11c15, is faster than that of LA, as demonstrated in vitro by Meynadier et al (2018), a-c Values within a row with different superscripts differ significantly at P < 0.05.…”
Section: Fatty Acids Related To Ruminal Biohydrogenationmentioning
confidence: 99%